Value creation as an approach to the management and control of rockburst damage in tunnels. (January 2019) - Moganedi, K.A.; Stacey, T.R.
Abstract: Energy absorbing support systems have the potential to contain or prevent rock mass damage on the periphery of underground excavations during a seismic event. Containing rockburst damage can protect employee safety, improve stakeholder relations and save money for the mine or tunnel owner. This is especially the case in deep tunnels, which may experience frequent seismicity and rockbursts. The financial consequences of rockbursts influence the potential value that energy absorbing support systems can provide in these mining and deep tunnel environments. In this paper, the potential value resulting from the use of different support systems in rockbursting conditions in deep tunnelling and mining environments is evaluated, and can be used as an approach to help facilitate the choice of support system.